An exploration of determinants of cyberchondria: A moderated mediation analysis. Issue 1 (22nd October 2020) - Zheng, Han; Chen, Xiaoyu; Fu, Shaoxiong
Abstract: Cyberchondria describes excessive or repeated health‐related information seeking on the Internet that is associated with increased emotional distress. Research on cyberchondria is still nascent. This study aims to propose a moderated mediation model to examine the relationships among intolerance of uncertainty, affective responses, e‐health literacy, and cyberchondria. Based on an online survey of 426 participants in China, the results suggest that intolerance of uncertainty is positively associated with cyberchondria, and affective responses partially mediate this association. Additionally, e‐health literacy negatively moderates the effect of affective responses on cyberchondria. Implications and limitations of this study are discussed.